2020
DOI: 10.1088/1361-6528/aba46d
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid-coated gold nanorods enhancing BMP-2 peptide delivery for chondrogenesis

Abstract: Bone morphogenic protein-2 (BMP-2) knuckle epitope peptide has been recently discovered and known to activate chondrogenesis. However, the applications of this soluble peptide remain very limited due to rapid diffusion resulting in poor cellular uptake into target cells. We herein designed nanoparticles made from hyaluronic acid functionalized gold nanorods (GNRs) to conjugate with thiolated BMP-2 knuckle epitope peptide via a two-step reaction. Hyaluronic acid was modified to have thiol functional groups to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For example, using liposomes to enclose gold NPs absorbed with fish oil, which increase the stability (Sarkar et al 2019 ). On the other hand, a growing number of drugs are being transported using gold NPs for their good biocompatibility and drug binding ability, such as hyaluronic acid, chondroitin sulfate, 2-[(aminocarbonyl)amino]-5-(4-fluorophenyl)-3-thiophenecarboxamide (TPCA-1), and rutin (Dwivedi et al 2015 , Sansanaphongpricha et al 2020 , Gul et al 2018 , Wang et al 2020 ).…”
Section: Nanoparticles That Have Shown Cartilage Protective Effectsmentioning
confidence: 99%
“…For example, using liposomes to enclose gold NPs absorbed with fish oil, which increase the stability (Sarkar et al 2019 ). On the other hand, a growing number of drugs are being transported using gold NPs for their good biocompatibility and drug binding ability, such as hyaluronic acid, chondroitin sulfate, 2-[(aminocarbonyl)amino]-5-(4-fluorophenyl)-3-thiophenecarboxamide (TPCA-1), and rutin (Dwivedi et al 2015 , Sansanaphongpricha et al 2020 , Gul et al 2018 , Wang et al 2020 ).…”
Section: Nanoparticles That Have Shown Cartilage Protective Effectsmentioning
confidence: 99%
“…The proliferation and differentiation of BMSCs can be considered as independent programmable processes, and controlling these processes in a predictable manner is crucial to regeneration of the desired tissue type. It has been reported that gold nanomaterials, mainly AuNPs, promoted osteogenic and chondrogenic differentiation through their effects on BMSCs (Yi et al, 2010;Sansanaphongpricha et al, 2020). The molecular mechanism mainly involved mitogen-activated protein kinase (MAPK), Wnt/β-catenin, and autophagy.…”
Section: Effect and Mechanism Of Gold Nanomaterials In Bone And Cartilage Tissue Engineering Promotion And Regulation Of The Differentiatmentioning
confidence: 99%
“…As for AuNRs, it is also easy to modify the surface of their surface. And with the help of other drugs or protein, AuNRs have been shown to promote chondrogenesis (Sansanaphongpricha et al, 2020). As can be seen from the examples above, gold nanomaterials are not only useful as therapeutic agents for cartilage disease but also have enormous potential in cartilage TE.…”
Section: The Protection For Cartilage Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Three days after surgery, the anastomoses with IGF-I coated sutures showed better anastomotic healing (histology appearance) and greater capacity to withstand biomechanical stress (busting pressure) than the control groups [ 23 ]. As an FDA-approved biologic, BMP-2 appears promising in promoting chondrogenesis and cartilage repair at pre-clinical setting [ 27 , 28 , 29 ]. The current study with BMP-2 coating on the resorbable sutures provides evidence to further support the theory that growth factors can be successfully introduced to a local tissue environment by coating suture material.…”
Section: Discussionmentioning
confidence: 99%